2010
DOI: 10.1007/s11248-009-9353-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of real time PCR assays for detection and quantification of transgene DNA of a Bacillus thuringiensis (Bt) corn hybrid in soil samples

Abstract: Real time PCR assays were developed to detect and quantify the transgene DNA of a commercially released Bacillus thuringiensis (Bt) corn (Zea mays L.) hybrid (DKC42-23), which was derived from the event MON863 and also carried a neomycin phosphotransferase gene (the nptII gene). We applied the real time PCR assays to investigate the persistence of the transgene DNA in a field trial grown with DKC42-23 over 3 years, in combination with bacterial natural transformation. The results showed that under continuous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In Bt (Cry3Bb1) corn grown in monoculture for three years in Ontario, Canada, Zhu et al (2010) detected the neomycin phosphotranferase (nptII) gene, an antibiotic-resistance gene commonly used as a marker in GM plants, in soil throughout the year. However, there was no evidence of transfer of this gene to soil bacteria .…”
Section: Bt Trait Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bt (Cry3Bb1) corn grown in monoculture for three years in Ontario, Canada, Zhu et al (2010) detected the neomycin phosphotranferase (nptII) gene, an antibiotic-resistance gene commonly used as a marker in GM plants, in soil throughout the year. However, there was no evidence of transfer of this gene to soil bacteria .…”
Section: Bt Trait Effectsmentioning
confidence: 99%
“…Lawhorn et al, 2009) although some negative effects were reported after four years of Bt cotton (Gossypium hirsutum L.) monoculture (Chen et al, 2011). The neomycin phosphotranferase (nptII) gene, an antibiotic-resistance gene commonly used as a marker in GM plants, was detected in soil throughout the season in Bt (Cry3Bb1) corn grown in monoculture for three years (Zhu et al, 2010). However, there was no evidence of transfer of this gene to soil bacteria .…”
Section: Introductionmentioning
confidence: 99%